Changing Patient Expectations Decreases Length of Stay in an Enhanced Recovery Program for THA. Issue 2 (February 2018) - Tanzer, Dylan; Smith CRA, Karen; Tanzer, Michael
Abstract: Background: The implementation of care pathways in hip arthroplasty programs has been shown to result in a decreased length of stay (LOS), but often multiple elements of a care pathway are implemented at the same time. As a result, it is difficult to understand the impact each of the individual modifications has made to the patient's prepathway care. In particular, it is unknown what the role of patient expectations pertaining to anticipated LOS alone is on the LOS after primary THA. Questions/purposes: (1) Does changing the patient's expectations regarding his or her anticipated LOS, without intentionally changing the rest of the care pathway, result in a change in the patient's LOS after primary THA? (2) Is the resultant LOS associated with the patient's age, gender, or day of the week the surgery was performed? Methods: We retrospectively compared the LOS in 100 consecutive patients undergoing THA immediately after the implementation of a 4-day care pathway (4-day Group) with 100 consecutive patients, 3 months later, who were also in the same pathway but were told by their surgeon preoperatively and in the hospital to expect a LOS of 2 days (2-day Group). Aside from reeducation by the surgeon, there was no difference in the surgery or intentional changes to the intraoperative or postoperative management of the two groups. Only the patient and the surgeon were made aware of the accelerated discharge plan. We compared the LOS between the two groups and the number of patients who met their discharge goal. As well, the ability to meet the discharge goal for each group was further determined based on age, gender, and day of the week the surgery was performed. Results: Overall, patients in the 2-day Group had a shorter LOS than those in the 4-day Group (2.9 ± 0.88 days versus 3.9 ± 1.71 days; mean difference 1 day; 95% confidence interval [CI], 0.60-1.36; p = 0.001). In the 2-day Group, the LOS was 2 days in 32% compared with 8% in the 4-day Group (odds ratio, 4.0; 95% CI, 1.76-9.11; p < 0.001). Men in the 4-day Group had a shorter LOS than women (3.4 ± 1.22 days versus 4.2 ± 1.89 days; mean difference 0.8 days; 95% CI, 0.17-1.78; p = 0.019), but there was no difference in LOS by gender in the 2-day Group (2.8 ± 0.81 days versus 3.1 ± 0.93 days; mean difference 0.3 days; 95% CI, -0.14 to 0.61; p = 0.219). For all patients > 40 years and < 90 years of age, a greater percentage of patients in the 2-day Group went home by postoperative day 2 than those in the 4-day Group (32% compared with 7%; odds ratio, 4.6; p < 0.001). In both groups, there was no difference in the LOS if the surgery was on Friday compared with an earlier day of the week (4-day Group: 3.4 ± 0.67 days versus 4.0 ± 1.80 days; p = 0.477 and 2-day Group: 2.8 ± 0.62 days versus 3.0 ± 0.93 days; p = 0.547). Conclusions: We found that a surgeon who sets a clear expectation in terms of LOS could achieve a reduction in this parameter. Although it is impossible to be certain in the context of a retrospective study whether other caregivers adjusted the pathway in response to the surgeon's preferences, and we suspect this probably did occur, this still points to an opportunity on the topic of expectations setting that future studies should explore. This study highlights the influence patient education and expectations has on the effectiveness of care pathways in THA as well as the importance of continuous reinforcement of discharge planning both preoperatively and in the hospital. Level of Evidence: Level III, therapeutic study.